Case Report: A case of complex cortical dysplasia with central precocious puberty onset - Guo, Chong; Chen, Chunmei; Wang, Xinrui; Lin, Kaiwu; Guo, Jingmin; Ge, Pin (Frontiers in Pediatrics, 2025)
A mutation rendering microtubulin and microtubule-associated proteins ineffective leads to a tubulinopathy known as complex cortical dysplasia (CCD), characterized by clinical heterogeneity and a variety of cortical brain developmental abnormalities. These often commence with intellectual disability, epileptic seizures, and motor disorders. In this case, we present a 6-year-old child with CCD whose symptoms began with central precocious puberty. Whole-exome sequencing uncovered a TUBB2B gene heterozygous mutation, NM_178012.5:c.74G > A (p.Ser25Asn). To our knowledge, this mutation has not been previously documented. Computational structural analysis indicated that this variant alters the hydrogen bonding between Ser25 and Trp21, Gly29, and Ile30, thus modifying the secondary structure and function of the protein, contributing to the child's unique clinical presentation. These findings expand the range of TUBB2B gene variants and offer a direction for the precise treatment of this child, underscoring the importance of brain magnetic resonance imaging in children with central precocious puberty.